2015
DOI: 10.1021/jf504146t
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsions Based on a Sunflower Lecithin–Tween 20 Blend Have High Capacity for Dissolving Peppermint Oil and Stabilizing Coenzyme Q10

Abstract: The objectives of the present study were to improve the capability of microemulsions to dissolve peppermint oil by blending sunflower lecithin with Tween 20 and to study the possibility of codelivering lipophilic bioactive compounds. The oil loading in microemulsions with 20% (w/w) Tween 20 increased from 3% (w/w) to 20% (w/w) upon gradual supplementation of 6% (w/w) lecithin. All microemulsions had particles of <12 nm that did not change over 70 d of storage at 21 °C. They had relatively low Newtonian viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…In comparison, rapeseed lecithin mixed with Quillaja saponins was able to stabilize the lipids at pH 3 (Figure D), showing that the mixed system increased the solubility of the lecithin product in aqueous medium. This is an agreement with a recent study showing that sunflower lecithin in a mixture with Tween 20 dramatically increased the dissolution of peppermint oil compared to just Tween 20 alone (Chen and others ). Mixing lecithin with other surfactants can also provide synergistic action: Das and Mitra () blended lecithin with a nonionic surfactant Triton X‐100, thus increasing the solubilization capacity of the formed microemulsions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison, rapeseed lecithin mixed with Quillaja saponins was able to stabilize the lipids at pH 3 (Figure D), showing that the mixed system increased the solubility of the lecithin product in aqueous medium. This is an agreement with a recent study showing that sunflower lecithin in a mixture with Tween 20 dramatically increased the dissolution of peppermint oil compared to just Tween 20 alone (Chen and others ). Mixing lecithin with other surfactants can also provide synergistic action: Das and Mitra () blended lecithin with a nonionic surfactant Triton X‐100, thus increasing the solubilization capacity of the formed microemulsions.…”
Section: Resultssupporting
confidence: 93%
“…Mixing lecithin with other surfactants can also provide synergistic action: Das and Mitra () blended lecithin with a nonionic surfactant Triton X‐100, thus increasing the solubilization capacity of the formed microemulsions. These studies show that by mixing different surfactants, the hydrophilic–lipophilic balance and the solubility of the mixed surfactant system in aqueous and emulsion based systems can be tuned (Das and Mitra ; Chen and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar T max values (time to maximum plasma CoQ 10 concentration) was around 1.5 and 1.7 h for CoQ 10 -enriched nanoemulsions and CoQ 10 crystal suspensions, but the nanoemulsion had about 1.7-fold higher AUC (area under the curve of plasma CoQ 10 concentration versus time) and C max (maximum plasma CoQ 10 concentration) than the crystal suspension. CoQ 10 -enriched nanoemulsions have also been prepared from a blend of sunflower oil and Tween 20 using spontaneous emulsification (Chen et al, 2015 ). This study suggested that the use of synthetic emulsifiers could be reduced for CoQ 10 -enriched nanoemulsion formation through a careful blending of natural and synthetic emulsifiers.…”
Section: Nanoemulsion Applications: Encapsulating and Improving Bioavmentioning
confidence: 99%
“…Thus, phytosterol oxidation will most likely be prevented by liposomal entrapment. Microemulsions are another delivery system that is gaining popularity in formulating or encapsulating bioactive components [92,93]. Similar to liposomes, microemulsions composed of oil, water, and surfactants (i.e., a colloidal dispersion) [83] can prevent oxidation of bioactive components [92,93].…”
Section: Formulation Of Phytosterols In Suitable Delivery Systemsmentioning
confidence: 99%